The Relationship between Strategic Leadership of School Administrators with School Effectiveness under the Office of the Secondary Education Area 21 - Littarak, Sangrawee; Choeybal, Panayuth; Charuchit, Pimporn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of the research article were 1) to study the level of the strategic leadership of school administrators, 2) to study the level of effectiveness of schools, 3) to study the relationship between the strategic leadership of school administrators and effectiveness of schools under the Office of the Secondary Education Service Area 21. The sample consisted of under the Office of the Secondary Education Service Area 21, 325 teachers by stratified random sampling. The research instruments were strategic leadership questionnaire and effectiveness of schools questionnaire. The statistical techniques employed in this analysis were frequency, percentage, mean, standard deviation and Pearson product moment correlation coefficient. The results were as follows : 1)The strategic leadership of school administrators under the Secondary Education Service Area 21 was at a high level. The highest level of leadership is strategic direction. 2) The effectiveness of schools under the Secondary Education Service Area 21 was at the highest level. The highest level of effectiveness of schools institutions is the ability to solve problems in schools. 3) The strategic leadership of school administrators and the effectiveness of schools under the Secondary Education Service Area 21. Have a relationship with statistical significance at 0.01 level in all aspects.